Streptococcal toxic shock syndrome with primary group A streptococcus peritonitis in a healthy female - Ahsan Wahab; Bilal Nasir (Greater Baltimore Medical Center, 2018)
A 47-year-old female with a history of chronic alcoholism presented with nausea, vomiting and mild epigastric tenderness. She reported subjective fever, abdominal fullness and loose, watery stools and had stable vitals on arrival. Examination was positive for mild epigastric tenderness with hepatic enlargement. Computed tomography of the abdomen showed circumferential thickening of the stomach wall, lower esophagus and the first part of the duodenum in addition to peritoneal ascites. She was admitted for alcohol-related gastritis, acute alcoholic hepatitis, and acute kidney injury. She was started on fluid resuscitation and supportive management. After 8-hours, the patient became hemodynamically unstable with subsequent intubation and fluid resuscitation. She was started on empiric antibiotics. Blood and ascitic fluid cultures were obtained showing group A beta-hemolytic streptococci (GAS). The patient was diagnosed with primary GAS peritonitis along with diffuse gastritis and streptococcal toxic shock syndrome. No cutaneous source of Streptococcus pyogenes was identified, and there was no personal or family history of streptococcal pharyngitis. Antibiotics were switched to IV ampicillin and clindamycin. However, the patient continued to deteriorate and succumbed to death within 2-days.